Culturing and Neuronal Differentiation of Human Dental Pulp Stem Cells - Goorha, Sarita (Curr Protoc Hum Genet, 2017)
A major issue in studying human neurogenetic disorders, especially rare syndromes affecting the nervous system, is the ability to grow neuronal cultures that accurately represent these disorders for analysis. Although there has been some success in generating induced pluripotent stem cells (iPSC) from both skin and blood, there are still limitations to the collection and production of iPSC from these biospecimens. We have had significant success in collecting and growing human dental pulp stem cells (DPSC) from exfoliated teeth sent to our laboratory by the parents of children with a variety of rare neurogenetic syndromes. This protocol outlines our current methods for the growth and expansion of DPSC from exfoliated (baby) teeth. These DPSC can be differentiated into a variety of cell types including osteoblast, chondrocytes and mixed neuron and glial cultures. Here we provide our protocol for the differentiation of early passage DPSC cultures into neurons for molecular studies.